2015
DOI: 10.1002/ceat.201500115
|View full text |Cite
|
Sign up to set email alerts
|

Segmented Flow‐Based Multistep Synthesis of Cadmium Selenide Quantum Dots with Narrow Particle Size Distribution

Abstract: A continuous-flow microreactor was used to synthetize II-VI semiconductor quantum dots (CdSe). In order to improve the size distribution of the nanoparticles, the synthesis was carried out in a two-step procedure. A seed solution was obtained in a separate nucleation step, followed by a controllable growth step. Quantum dots that are synthesized with the two-step method show a much narrower size distribution in comparison to those obtained in a conventional batch synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In contrast to organic chromophores, they show higher photochemical stability, narrower optical emission spectra, larger molar absorption coefficients, and the ability to tune the emission wavelength by the size of the nanoparticle, which are the decisive reasons the synthesis of inorganic QDs advanced from lab scale batch synthesis towards process engineering practice [3]. In this context, the usage of continuous micro-flow reactors has proven to be a method for reproducible production of many semiconductor nanoparticles systems with high quality [4][5][6]. The next stage towards integration of this material into a new matrix or subsequent synthesis protocols is its purification.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to organic chromophores, they show higher photochemical stability, narrower optical emission spectra, larger molar absorption coefficients, and the ability to tune the emission wavelength by the size of the nanoparticle, which are the decisive reasons the synthesis of inorganic QDs advanced from lab scale batch synthesis towards process engineering practice [3]. In this context, the usage of continuous micro-flow reactors has proven to be a method for reproducible production of many semiconductor nanoparticles systems with high quality [4][5][6]. The next stage towards integration of this material into a new matrix or subsequent synthesis protocols is its purification.…”
Section: Introductionmentioning
confidence: 99%
“…Manipulating liquid droplets with mini volume in microchannels has attracted a lot of attention for both potential applications and fundamental research, such as synthesis of materials, drug delivery and release, , cell culture, and droplet PCR chips. Usually, techniques for droplet manipulation in microchannels can be divided into passive and active methods . Passive droplet manipulation refers to using channel geometry to achieve droplet generation and movement and other functions. For example, Dhiman et al demonstrated the transport of aqueous droplets in an oil-submerged diverging groove, which was realized by a differential Laplace pressure between the leading and trailing interfaces of a droplet.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] Several groups have utilized microuidic systems for continuous syntheses of nanoparticles of various types and shapes, [32][33][34][35][36][37][38] QDs [39][40][41][42][43] and core-shell systems. [44][45][46] Various actions have resulted in narrow PSDs, such as the use of segmented ow, [47][48][49] multistage 48,50 and high-temperature high-pressure reactors, 43,51,52 the latter enabling syntheses under supercritical conditions. While the use of multistage reactors allows for separation of nucleation and growth, the other two systems aim at minimization of the effects of solvent viscosity and axial dispersion.…”
Section: Introductionmentioning
confidence: 99%